Biodegradation of MC252 oil in oil:sand aggregates in a coastal headland beach environment - Elango, Vijaikrishnah; Urbano, Marilany; Lemelle, Kendall R.; Pardue, John H. (Frontiers in Microbiology, 2014)
Biodegradation potential of MC252 in oil:sand aggregates, termed surface residue balls (SRBs), was examined using multiple lines of evidence on a heavily-impacted coastal headland beach in Louisiana, USA. SRBs were sampled over a 16-month period on the supratidal beach environment where reasonable control existed on the residence time of the aggregates on the beach surface. PAH and alkane concentration ratios were measured including PAH/C30-hopane, C2/C3 phenanthrenes, C2/C3 dibenzothiophenes and alkane/C30-hopane and demonstrated unequivocally that biodegradation was occurring in SRBs in the supratidal. These biodegradation reactions occurred over time frames relevant to the coastal processes moving SRBs off the beach. In contrast, submerged oil mat (SOM) samples did not demonstrate chemical changes consistent with biodegradation. Review and analysis of additional biogeochemical parameters suggested the existence of a moisture and N-limited biodegradation regime on the supratidal beach environment. At this location, SRBs possess moisture contents < 2% and molar C:N ratios from 131-323, well outside of optimal values for biodegradation in the literature. Despite these limitations, biodegradation of PAHs and alkanes proceeded at relevant rates (2-8 year-1) due in part to the presence of degrading populations, i.e., Mycobacterium sp., adapted to these conditions. For SOM samples in the intertidal, an oxygen and salinity-impacted regime is proposed that severely limits biodegradation of alkanes and PAHs in this environment. These results support the hypothesis that SRBs deposited at different locations on the beach have different biogeochemical characteristics (e.g., moisture; salinity; terminal electron acceptors; nutrient; and oil composition) due, in part, to their location on the landscape.